Crystal Schottisch - WM. Byerly::::::::: (Firth, Pond & Co., (WM. A. Pond & Co.))
Piano score, 5 p. cover title: To Theodore Sedgwick, Esq., The Crystal Schottisch cover lithograph in color of the New York Crystal Palace number 4 noted on cover, possibly arranged for 4 hands.